OPTIMALISASI PEMANFAATAN ASET DAERAH SEBAGAI SUMBER PAD DI DINAS PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA SEMARANG TAHUN 2013 – 2015 - Soewanto Adhi (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2016)
Implementation of regional autonomy gives greater authority to local government to regulate the area, in accordance with Regulation 58 of 2005 Section 1 Item 5 About Financial Managemen area. Assets area became an important part of a local authority, for assets owned an area has the fuction to support the implementation of government activities and can provide contribution to PAD. Their asset management weak cause asset was not maintained and not utilized optimally and can also be done annexation by a third party, because of weak oversight of local government itself, so it need to optimize the utilization to maintain an assets always utilized and beneficial for the region itself. Another objective of this study was to determine whether the implementation of utilization in Semarang has been carried out according to the procedure or not. From the results of research in DPKAD Semarang be known that during this SKPD has tried as much as possible to optimize the use of assets in Semarang so as to contribute to PAD Semarang.